Pattern of Haemotological Disorders Diagnosed by Bone Marrow Examination at a Paediatric Hospital in Larkana Pakistan (Medical Forum Monthly, 2024)
Background: Bone marrow examination is an integral part for establishing the diagnosis of haematological disorders in association with clinical and other routine laboratory tests. Objective: To evaluate the frequency and pattern of haematological disorders in children at a tertiary care hospital in Larkana. Study Design: Descriptive study. Place and Duration: The study was conducted at children hospital and pathology department of Chandka Medical College Larkana from Jan: 2008 to Dec: 2010. Patients and Methods: Marrow aspirates were collected from children under the age of 15 years as per guidelines recommended by international council for standardization in haematology (ICSH). Smears obtained were stained with Romanowsky stains and examined under light microscope. Results: Bone marrow examination reports of 271 patients ranged from 2 months to 15 years, with male /female ratio of 1.6:1 were analyzed. Malignant disorders were seen in 36.5% and non malignant disorders in 59.8% of children. Amongst the malignant haematological disorders, acute lymphoblastic leukaemia (ALL) cases were 64 (23.6%) and was found to be most common disorder, followed by lymphoma 7 (2.6%) cases and acute myeloid leukaemia (AML) 6 cases (2.2%). In non malignant disorders aplastic anaemia was the most common 40 (14.8%) cases, followed by iron deficiency anaemia 30 (11%) cases. The megaloblastic anaemia was least common seen only in 8 (3.0%) cases. Other non malignant disorders were idiopathic thrombocytopenic purpura (ITP) 71 (26.2%) cases and malaria 4 (1.5%) cases. Conclusion: Appropriate diagnosis can not be made in haemotological disorders of childhood without bone marrow examination.